Design of Breakwaters to Minimize Greenwater Loading on Bow Structures of Fixed Vessels - Lim Jun An; Mohammed Abdul Hannan (Fluids, 2021)
Greenwater (splashing of water on the deck) loading is a classical problem faced by designers of ship-shaped vessels, which becomes even worse when the vessel operates in harsh weather conditions for an extended period of time. Installation of breakwaters on the deck can play a crucial role in minimizing this impact. However, research on the design and optimization of the breakwater is still in its infancy, and this study aims at shedding further light on this area by proposing and analysing the effectiveness of three breakwater designs on a fixed box-shaped vessel. The commercial CFD software ANSYS Fluent is used for this investigation. The design model (without breakwater) was validated at first against experimental results of greenwater splashing, before performing the actual simulations with the proposed breakwater design. A vertical plate is used as the deck structure, and the greenwater pressure at several locations on that plate is measured to compare the effectiveness of various breakwater designs. Overall, breakwaters with openings (perforations, grillages, etc.) were found to be more effective in minimizing the pressure generated by the greenwater. Nevertheless, there is significant room for improvement on breakwater designs, and some topics for further research are also suggested in this regard.